The Epidemiologic, Clinical and Laboratory Findings of Patients with Guillain Barre´ Syndrome in Southern Iran Since 2007 to 2012 - Abbas Rahimi jaberi; Alireza Manafi; Ali Mossallaiepoor; Mohammad mehdi Ebrahimi; Sahar Khazforoosh; Shadan Shirazi zade mehraban; Shideh Aramesh fard; Parivash Ahmadfard; Javad Salami; N Mousaei (Fasa University of Medical Sciences, 2013)
Background ;Objective: Guillain Barre´ syndrome is an autoimmune neuropathy which is considered to be the most acute areflexic paralysis with albuminocytologic dissociation.1 Areflexia or hyporeflexia, pain in limbs, autonomic dysfunction, progressive bilateral and symmetric weakness of limbs, numbness and paresthesia are described as the clinical features of GBS.Nevertheless, with having less prognosis, the treatment is usually effective. Most patients diagnosed with GBS were previously infected with CMV or C.jejuni. Subtypes of the disease are either Axonal or Demyelinating. Due to increase use of Guillain Barre´ in south of Iran, the present study has done a retrospective study on the epidemiology of Guillain Barre in the south part of Iran.Materials & Methods: We performed our retrospective study in Namazi hospital in Shiraz, Iran. Medical records were analyzed using computer and were presented through percentages.Results: 214 patients were studied in which 119(55.6%) of them were men and 95 (44.4%) of them were women. 15 % of the participants had respiratory disturbance and 5.1% of them had histories of common cold and 1.4 of them were vaccinated before the study. Moreover, six people had died but 208 patients were treated and healed either by prescribed dosage of IVIg (69.2%) or plasmapheresis (24.3%) and one patient was also seen who had HIV virus.Conclusion: This study provides more details on the epidemiology of GBS in Shiraz, and south of Iran. Our study also revealed the difference in pattern of GBS in Iran and other countries. however, there is still a need for further clarification of the issues.